Analisis kebutuhan bahan ajar LKPD untuk meningkatkan keaktifan belajar siswa - Br Kembaren, Febrina; ., Nuryadi; Nurwoko, Iman (CV. Information Technology Training Center - Indonesia (ITTC), 2024)
The aim of this research is to examine the need for Ethnomathematics-based LKPD (Learner Worksheets) to increase student learning activity. The subjects of this research were class VIII students at one of the State Middle Schools in Yogyakarta. Data collection techniques use observation, distribution of questionnaires and test results that use indicators of learning activity. This research has several results. First, the remaining 81% had difficulty understanding mathematical material. Second, 84% of students are not active in the mathematics learning process in class. Third, 69% of students said that the learning media that makes learning mathematics easier is LKPD, 22% of students chose books as a medium that makes learning mathematics easier and 9% of students chose other learning media. Fourth, the results obtained were that 81% of students were interested if the triangle and quadrilateral teaching materials were packaged in the form of Ethnomathematics-based LKPD to increase students' learning effectiveness. Apart from that, the test results showed that there were no students who obtained the Minimum Completeness Criteria (KKM) score. Therefore, the development of Ethnomathematics-based LKPD is needed to increase student learning activity.